Seventh IEEE International Workshop on Policies for Distributed Systems and Networks (POLICY'06)
DOI: 10.1109/policy.2006.37
|View full text |Cite
|
Sign up to set email alerts
|

Trust Meta-Policies for Flexible and Dynamic Policy Based Trust Management

Abstract: It is possible to impose the will of the user or administrator through the specification of policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In our trust model we adopt the widely accepted definition of trust as relationship between a Trustor and a Trustee [16,17]. We define trust as the measurement of the belief from a trusting party point of view (trustor) with respect to a trusted party (trustee) focused on a specific trust aspect that possibly implies a benefit or a risk [9].…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…In our trust model we adopt the widely accepted definition of trust as relationship between a Trustor and a Trustee [16,17]. We define trust as the measurement of the belief from a trusting party point of view (trustor) with respect to a trusted party (trustee) focused on a specific trust aspect that possibly implies a benefit or a risk [9].…”
Section: Trustmentioning
confidence: 99%
“…Some trust models associate trust relationships with an isolated or combined measurement of the concepts of honesty, credibility, reputation, usability, competence, fit for purpose, reliability, and quality [20] [17]. Our trust model captures precisely all this different concepts with the definition of the different trust types, recommendations, and trust aspects.…”
Section: Trustmentioning
confidence: 99%
“…Conditional statements take the form if <conditions to be satisfied>, then <execute an action>. Examples are presented in [7,8,25,26]. Policies described by such statements are verified and validated, as discussed in [27].…”
Section: Related Workmentioning
confidence: 99%
“…We formalize trust as a relationship between two entities, the Trustor and the Trustee, as widely accepted by the literature [48,2,68,107]. In this thesis, we define trust as the measurement of the belief from a trusting party point of view (trustor) with respect to a trusted party (trustee) focused on a specific trust aspect that possibly implies a benefit or a risk.…”
Section: Trust Management Modelmentioning
confidence: 99%
“…Other trust concepts are also important and are considered future work in this thesis. A list of possible trust concepts and their correlations based on user studies can also be found in [107].…”
Section: Trust Management Modelmentioning
confidence: 99%